The Nexus Between Teacher Professional Identity And Some Socio-Demographic And Psychological Variables - Predrag Zivkovic (European Scientific Journal, ESJ, 2016)
As multidimensional concept, primarly relational rather then substantial, professional identity can be investigated in nexus with sociodemographic and psychological variables. On a sample of N= 284 active teachers in Serbia and in Montenegro, the author examined the prominence of various aspects of teachers professional identity (teaching practice, school and profession, student development, personal development, role anticipation, and commitment to roles), as well as their interrelationship with some psychological variables (self-esteem, self-assessment of their own success, satisfaction with family, and professional satisfaction) and sociodemographic variables (sex, place of residence, years of service, and financial status). The obtained results show that personal development is the most pronounced aspect of teachers’ professional identity and that role anticipation is the least pronounced one. Significant correlation has been found between different aspects of professional identity and individual psychological correlates. The results show that there is a possibility of predicting professional identity (the majority of measured aspects) based on a set of psychological predictors. The best predictor in all aspects of professional identity is professional satisfaction. Regarding the nexus with certain sociodemographic characteristics, an interesting finding is that years of service negatively correlated with most of the examined aspects of teachers’ professional identity. The results imply the need for further research of this phenomenon, with the inclusion of a number of psychological and social factors that are directly or indirectly related to the professional identity of teachers.